Zwitterionic Polydopamine-Coated Manganese Oxide Nanoparticles with Ultrahigh Longitudinal Relaxivity for Tumor-Targeted MR Imaging - Wang, Peng (Langmuir : the ACS journal of surfaces and colloids, 2019)
We present the design of antifouling zwitterion-functionalized manganese oxide (Mn3O4) nanoparticles (NPs) modified with folic acid (FA) for targeted tumor magnetic resonance (MR) imaging. In the current work, diethylene glycol-stabilized Mn3O4 NPs were initially prepared via a solvothermal approach, coated with polydopamine (PDA), fluorescently labeled with rhodamine B, conjugated with FA via amide bond formation, and finally covered with zwitterions of l-lysine (Lys). The thus-generated multifunctional Mn3O4 NPs display excellent water dispersibility and colloidal stability, good protein resistance ability, and desirable cytocompatibility. With the PDA and Lys modifications, the multifunctional Mn3O4 NPs own an ultrahigh r1 relaxivity (89.30 mM-1 s-1) and enable targeted tumor MR imaging, owing to the linked FA ligands. The designed antifouling zwitterion-functionalized Mn3O4 NPs may be employed as an excellent MR contrast agent for targeted MR imaging of other biological systems